The Growth and Stabilization Properties of Fiscal Policy in Malaysia - Rafiq, Sohrab (Washington, D.C. : International Monetary Fund, 2013)
This paper examines the size of the fiscal multiplier values generated in Malaysia. The results show that a government spending shock leads to broad positive economic effects. Although, the effectiveness of fiscal policy alters across macroeconomic states. The estimates show that since the Asian financial crisis the medium- and long-run effect of fiscal policy spending has declined. Some of this is down to greater credit availability and less investment spending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet